The arrangement - Kazan, Elia 1909-2003 (Avon Books)
This is the beginning of Elia Kazan?s 1969 film The Arrangement, based on his bestselling novel, and it?s soon clear that what we?re witnessing is the birth of a genre - the American Discontent Movie, later epitomised by John G. Avildsen?s Save The Tiger and Sam Mendes? American Beauty. Like the characters played by Jack Lemmon and Kevin Spacey, Eddie Anderson represents a tumour at the heart of American society which needs to be cut out. But whereas the later films end in despair and doom, The Arrangement is a wish-fulfillment fantasy. It?s about the precedence of art over commerce - the hero wants to be a writer but has been sidetracked into the sordid world of advertising where he has been busy designing a campaign to persuade the world that Zephyr cigarettes are clean